Effect of finishing and polishing techniques on the surface roughness of a nanoparticle composite resin - Vera Lucia Schmitt; Regina Maria Puppin-Rontani; Fabiana Scarparo Naufel; Danielle Ludwig; Julio Katuhide Ueda; Lorenço Correr Sobrinho (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the surface roughness of the resin Filtek Z350 (3M ESPE) after different finishing and polishing techniques. Methods: Sixty specimens of 7x2 mm were made and distributed in 6 groups (n=10), according to the technique employed: G1 (control) - polyester strip - no finishing or polishing; G2- multi-blade burs; G3- diamond burs 3195F and 3195FF; G4- Diamond Pro Discs (FGM); G5- Sof-Lex Discs (3M ESPE); G6- Robinson bristle brushes with pumice paste for 20 s and felt disc with 2-4 µm diamond paste for 30 s. The specimens were stored in artificial saliva at 37°C for 7 days. After the finishing and polishing techniques, surface roughness (Ra, µm) was measured using Surf-Corder profilometer SE 1700. Data were subjected to one-way ANOVA and Tukey's test at 5% significance level. Results: G3 presented the highest surface roughness mean value (0.61). G5 presented the lowest surface roughness mean value (0.15), but it was not significantly different from G1, G4 and G6. Conclusions: According to the obtained results, Z350 composite resin presented the lowest surface roughness when finishing and polishing systems were used (Sof-lex and Diamond Pro discs and Robinson bristle brush with pumice plus Diamond® felt disc with Diamond Excel® paste). The use of diamond burs (G3) resulted in the highest composite surface roughness. There was no significantly different between G1, G4, G5 and G6.